Risk subset of the survival for nasopharyngeal carcinoma patients with bone metastases: Who will benefit from combined treatment? - Cao, Xun; Han, Yujing; He, Liru; Xiang, Jin; Wen, Zhesheng (Oral oncology, 2011)
Bone metastasis from nasopharyngeal carcinoma (NPC) is the most frequent type of distant metastasis (DM). The purpose of this study was to elucidate survival, prognostic factors, and significant of treatment in NPC patients with bone metastasis. A total of 221 patients who developed single type of DM from NPC at the first failure after primary treatment were retrospectively recruited from January 1998 to October 2000. The correlation between disease-free interval (DFI) and clinicopathologic features was assessed by the Chi-square test. Univariate and multivariate analyses of clinicopathologic variables were performed using Cox proportional hazards regression models. Actuarial survival rates were plotted against time using the Kaplan–Meier method, and log-rank testing was used to compare the differences between the curves. The median overall survival (OS) of the whole cohort and bone metastatic NPC patients were 38.5 and 33.3months, respectively. After univariate and multivariate analyses of clinicopathologic variables, age, local recurrence, subsequent metastasis, DFI and treatment modality were independently significant prognostic factors. The outcomes of bone metastatic NPC patients in low- and high-risk subset were significantly different (49.5 vs. 19.4months, P<0.001). In stratified survival analysis, compared to chemotherapy alone, chemoradiotherapy (CRT) could benefit the patients in low-risk subset (P<0.001), but not those in high-risk subset (P=0.135). Our findings indicated that clinicopathologic variables could provide easily available prognostic factors for survival in NPC patients with bone metastasis. A subset of bone metastatic NPC patients would benefit from aggressive combined treatment and receive a long-term survival.